Re-positioning urban-based new villages in peninsular Malaysia towards sustainable living and a better quality of life - Phang, Siew Nooi *; Tan, Teck-Hong * (2013)
A study into the history of New Villages (NV) in Malaysia indicates that there was a purpose and use for NVs when they were established and developed in the early 1950s. While initial assistance from the federal government did contribute marginally to the growth of these NVs, however, through the years, they were left to fend for themselves. Ultimately, the growth pattern of these settlements showed conspicuous disparity in terms of economic prosperity and development. Those NVs nestled in semi urban and urban peripheries thrived and became robust, while those in the rural areas languished. Using a case study, this paper will explore and examine events that are challenging NVs in Malaysia which may alter the fate of NVs in the future. NVs in Malaysia today are at a cross-road between sustainable growth and fossilisation. This paper will describe the living condition and housing environment of the NVs and narrate the political affinity of the NV community based on their voting patterns in the past general elections and groundwork investigations. Any re-development plans for the NVs should be viewed as a part of the mainstream of national development which has sustainable living and a better quality of life as one of the objectives.